2014
DOI: 10.1111/caim.12085
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leadership and Performance in Chinese New Ventures: A Moderated Mediation Model of Exploratory Innovation, Exploitative Innovation and Environmental Dynamism

Abstract: This study advances prior theoretical research by examining the relationship between entrepreneurial leadership and new venture performance with the introduction of exploratory and exploitative innovations as mediating variables. To fully understand the influence process of entrepreneurial leadership, we argue that environmental dynamism should be considered. Data on 168 new ventures in China indicate that entrepreneurial leadership is positively related to both exploratory and exploitative innovations, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
205
1
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(233 citation statements)
references
References 109 publications
16
205
1
11
Order By: Relevance
“…Therefore, nurses’ successful IWB depends on their supervisors’ support throughout the innovation process, from exploring and generating a new idea to championing and implementing the idea (Kessel et al., ). This finding supports the contention that the influence of EL style varies with different dimensions of innovation behavior (Huang et al., ). More specifically, our findings provide new insights on the stronger effect of entrepreneurial leaders on nurses’ capacity to explore, generate, and implement new ideas than on championing new ideas.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, nurses’ successful IWB depends on their supervisors’ support throughout the innovation process, from exploring and generating a new idea to championing and implementing the idea (Kessel et al., ). This finding supports the contention that the influence of EL style varies with different dimensions of innovation behavior (Huang et al., ). More specifically, our findings provide new insights on the stronger effect of entrepreneurial leaders on nurses’ capacity to explore, generate, and implement new ideas than on championing new ideas.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings confirmed the hypothesized significant impact of EL on nurses’ IWB. This finding contributed some of the first empirical evidence on the influential effect of EL on IWB in public and private organizations (Huang et al., ; Kim et al., ). In particular, this finding extends previous studies that have long suggested the influential effects of EL on IWB in healthcare organizations (Ballein, ; Guo, ).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…41 The entrepreneurial leaders also redesign their members' perceptions of their competencies by involving them in developing new and innovative ideas, and building their confidence to implement these ideas. 88,89 The functional competencies of entrepreneurial leaders also empower them to intentionally inspire and regulate their members toward innovation. 25,90 The leaders of high-tech entrepreneurial-based organizations realize their vision through identifying and stimulating the potential competencies of their group members, enabling them to generate new ideas, and reshaping their behavior, thoughts, and attitudes of implementing new ideas.…”
Section: Theoretical Background Entrepreneurial Leadership and Innovamentioning
confidence: 99%